2003
DOI: 10.1046/j.1464-5491.2003.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

A postnatal fasting plasma glucose is useful in determining which women with gestational diabetes should undergo a postnatal oral glucose tolerance test

Abstract: In our population, a 6-week postnatal fasting plasma glucose is useful in determining which women with gestational diabetes should undergo an OGTT. Consequently we now perform OGTT only in women whose postnatal fasting plasma glucose is > or =6.0 mmol/l.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
0
26
1
1
Order By: Relevance
“…Five studies 22, 24, 29, 30, 32 compared the FBG ≥ 7.0 mmol/L (≥ 126 mg/dL)7 to a 2-hr 75-gm OGTT with a fasting threshold ≥ 7.8 mmol/L (≥ 140 mg/dL) and a 2-hr plasma glucose > 11.1 mg/dL (> 200 mg/dL) 21. (Tables 1 and 2) These studies consistently reported high specificity of the FBG (range: 94 to 99 percent) with very few “false positives.” (Figure 3) However, the sensitivities of the FBG alone ranged from 14 to 100 percent.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies 22, 24, 29, 30, 32 compared the FBG ≥ 7.0 mmol/L (≥ 126 mg/dL)7 to a 2-hr 75-gm OGTT with a fasting threshold ≥ 7.8 mmol/L (≥ 140 mg/dL) and a 2-hr plasma glucose > 11.1 mg/dL (> 200 mg/dL) 21. (Tables 1 and 2) These studies consistently reported high specificity of the FBG (range: 94 to 99 percent) with very few “false positives.” (Figure 3) However, the sensitivities of the FBG alone ranged from 14 to 100 percent.…”
Section: Resultsmentioning
confidence: 99%
“…Holt et al was the only study that reported a measure of reproducibility. The coefficient of variation for the plasma glucose assay was 1.2 percent at 3.3 mmol/L (59.4 mg/dL) and 1.5 percent at 16.5 mmol/L (297 mg/dL), which reflects low variability 24. No included studies compared the reproducibility of the FBG with the OGTT, which included a 2-hr plasma glucose value.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations